Creating An Environment Conducive To Effective Financial Risk Management In Nigeria’s Petroleum Industry - Ogulu, Christiana; Njomo, Louis; Arnolds, Cecil (Archives of Business Research, 2019)
The primary research objective of this study was to make a contribution to the financial risk management (FRM) in the petroleum industry of Nigeria by exploring the critical factors required to create an environment conducive to FRM success in that industry. A sample of 70 lower, middle and top managers from the Association of Senior Staff of the Petroleum Industry of Nigeria participated in the study. The FRM framework produced in this study improves on the current unintegrated FRM situation, which is characterised by reactionary responses to mathematical calculations of financial ratios. The improved framework provides a more comprehensive and holistic method of managing financial risks in the Nigerian petroleum industry. The study identified critical FRM areas to address in a firm and the implementation of plans to improve in these areas.